"It was only me against the world." Female African American Adolescents' perspectives on their sexual and reproductive health learning and experiences while in foster care: Implications for positive youth development. (November 2020) - Ross, Christina; Kools, Susan; Laughon, Kathryn
Highlights: Youth did not trust caregivers and often felt unheard and judged. Teen mothers perceived their children as strengths/motivators. Fear of caregiver judgment lead youth to obtain sex education online. Some youth learn about sex because of sexual abuse. Most youth did not have a supportive relationship with their health care provider. Abstract: Female African American adolescents experience high rates of sexually transmitted infections and unintended pregnancies. However, little is known about the sexual and reproductive health (SRH) needs of youth in foster care. This study explored the experiences of female African American/Black youth in foster care related to their SRH disparities and needs. The purposive sample was 16 female adolescents, ages 18–20 years old, with a history of foster care placement. Participants were recruited from a metropolitan area in Virginia. This study used a qualitative descriptive design with semi-structured in-depth interviews lasting an average of 1 h. The transcribed interviews underwent inductive thematic analysis, and four prominent themes emerged: caregiver barriers, facilitators, sources of information, and recommendations for caregivers. Results indicated that youth felt unsupported, relied on their strengths to seek information related to SRH, and provided their advice on communication about SRH with youth. The findings from this study will provide direction on how caregivers, health-care workers, social services staff, and community members can better support the SRH needs of young women in foster care.